OPTIMALISASI PERAN KELEMBAGAAN PERENCANAAN SUMBER DAYA ALAM DALAM PENANGANAN PERMASALAHAN PENANAMAN MODAL - Andi Setyo Pambudi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
The investment dynamics in Indonesia are generally related to internal and external problems, which are often responded to by changes in regulations and policies. It is reasonable considering that Indonesia's Ease of Doing Business (EODB) currently is still low, ranking 73 out of 190 countries, which in the context of the ASEAN region is still ranking 6 out of 8 countries. Law and policies drawn up since President Joko Widodo's leadership have brought about significant changes as indicated by the realization of investment, both domestic (PMDN) and foreign (PMA), although slightly corrected as a COVID-19 outbreak result. Foreign capital is expected to have a direct impact on national economic growth. If we take a closer look, since Law No. 25 of 2007 (UUPM) came into effect, the Indonesian economy has gradually improved. Natural resources, as one of the sectors in investment, require planning that can adapt to changes, both in substance, regulations, and institutions. The portrait of investment and its problems are appealing to review when associated with existing institutions. From the perspective of policymakers, optimizing institutional potential related to investment is needed as a strategic step of services improvement to the public. This paper aims to present a portrait of investment problems, natural resource planning institutions related to current investment and identify development potential towards optimizing roles in supporting national development. The method used in the analysis is based on a literature review, both from previous research also regulations and policies in Indonesia. The analysis results are policy recommendations and institutional recommendations for investment relevant to current conditions to be followed up by stakeholders and policymakers in developing competitive and sustainable investment.